Assessment of Diesel Engine Performance, Combustion and Emission Characteristics with Supplementation of Neem Oil Methyl Ester Along With EGR - Ravi Kathirvel and Vijayabalan Palanimuthu (Nature Environment and Pollution Technology, 2022)
Biodiesel generated from a variety of non-edible feedstocks has gained widespread acceptance as a limited diesel fuel alternative in compression ignition engines. For the reliable implementation of biodiesel in commercial sectors, its effect on engine combustion, emission, and performance needs to be examined experimentally. In this study, 10% (N10) and 20 % (N20) Neem oil methyl ester (NME) blends were tested in a direct injection 4-stroke single-cylinder diesel engine incorporated with 5% and 10% exhaust gas recirculation (EGR). At maximum load conditions, Brake thermal efficiency (BTE) was found highest for N20 by 7.2%, and also Brake specific energy consumption (BSEC) was reduced by 11.4% for N20 as compared to diesel. Meanwhile, the incorporation of EGR deteriorates the performance parameters for the N20 blend. The results of emission analysis showed that oxides of nitrogen (NOx) increased with the addition of biodiesel whereas the addition of EGR diminished the NOx value for both biodiesel blends at all loading conditions. Unburnt hydrocarbon (UHC), Carbon monoxide (CO), and smoke emissions decreased by 40.6%, 31.2%, and 29.6% for the N20 blend respectively at full load when compared to diesel. Interestingly, when EGR was provided, CO, UHC, and smoke density values are increased for both N10 and N20 blends at all loading conditions, however lower than diesel operation.